Highly invasive tree species are more dependent on mutualisms - Moyano, Jaime (2020)
Why some species become invasive while others do not remains an elusive question. It has been proposed that invasive species should depend less on mutualisms, because their spread would then be less constrained by the availability of mutualistic partners. We tested this idea with the genus Pinus, whose degree of invasiveness is known at the species level (being highly and negatively correlated with seed size) and which forms obligate mutualistic associations with ectomycorrhizal fungi (EMF). Mycorrhizal dependence is defined as the degree to which a plant needs the mycorrhizal fungi to show the maximum growth. In this regard, we use plant growth response to mycorrhizal fungi as a proxy for mycorrhizal dependence. We assessed the responsiveness of Pinus species to EMF using 1206 contrasts published on 34 species, and matched these data with data on Pinus species invasiveness. Surprisingly, we found that species which are more invasive depend more on mutualisms (EMF). Seedling growth of species with smaller seeds benefited more from mutualisms, indicating a higher dependence. A higher reliance on EMF could be part of a strategy in which small-seeded species produce more seeds that can disperse further, and these species are likely to establish only if facilitated by mycorrhizal fungi. On the contrary, big seeded species showed a lower dependence on EMF, which may be explained by their tolerance to stressful conditions during establishment. However, the limited dispersal of larger seeds may limit the spread of these species. We present strong evidence against a venerable belief in ecology that species that rely more on mutualisms are less prone to invade, and suggest that in certain circumstances greater reliance on mutualists can increase spread capacity.